Praktikalitas Lembar Kerja Peserta Didik Elektronik (E-LKPD) Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Materi Sistem Pencernaan Kelas XI SMA - Nola Sukma; Wan Syafii; Darmadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to determine the practicality level of the Electronic Student Worksheet (E-LKPD) in improving students' critical thinking skills on the digestive system material for Grade XI high school students. The problem underlying this research is the low level of students' critical thinking skills and the absence of electronic teaching materials based on critical thinking skills that meet students' needs. This is development research using the ADDIE model but limited to the development stage. Instruments used include expert validation, teacher and student response questionnaires, and critical thinking skill tests in the form of essay questions. Data was obtained from Grade XI students of SMAN 1 Kelayang and analyzed using descriptive quantitative methods. Validation results showed that the E-LKPD is categorized as valid with an average score of 3.2. A limited trial indicated a very high level of practicality, both from teachers (89.58%) and Grade XII students (86.31%). The practicality test by Grade XI students during learning activities showed a score of 85.28%, classified as very practical. The test results showed an increase in students’ critical thinking skills from 33.97% to 61.90%, with an average N-gain score of 0.42 (moderate category). Thus, the E-LKPD is considered feasible and highly practical to be used as a teaching material to improve students’ critical thinking skills in the topic of the digestive system